New Zealand dental therapists' beliefs regarding child maltreatment. (28th August 2014) - Tilvawala, Dhara; Murray, Colleen; Farah, Rami; Broadbent, Jonathan M.
Abstract Objective: To investigate dental therapists' perceptions of the problem of child maltreatment and their roles in child protection, their experience/recollections of past training, and how frequently they suspect (and report) abuse or neglect. Methods: Ethical approval was obtained and a postal survey was conducted of all 643 New Zealand (NZ) dental therapists with current annual practising certificates and known addresses. Data were double‐entered for accuracy and analysed in SPSS version 20.0. Results: The participation rate was 49.8% (N=320 of 643). Most dental therapists (77.1%) believed rates of death due to child abuse were greater in NZ than other countries. More than 81% desired more continuing professional education courses. During the past year, 18.1% had suspected physical abuse, 30.9% had suspected neglect and 53.1% had suspected dental neglect in their patients. About half of all suspected cases were never reported. The major barrier was a fear of mistakenly reporting a non‐abuse case. Conclusions and implications: Most NZ dental therapists believe they have an important role in child protection, yet their suspicions are frequently unreported. Dental therapists may benefit from appropriate support and clear advice from their employers when dealing with suspected cases of maltreatment.